Physiologically‐Based Pharmacokinetic Modeling for the Prediction of a Drug-Drug Interaction of Combined Effects on P‐glycoprotein and Cytochrome P450 3A - Yukio Otsuka; Mary P. Choules; Peter L. Bonate; Kanji Komatsu (Wiley, 2020)
Direct oral anticoagulants, such as apixaban and rivaroxaban, are important for the treatment and prophylaxis of venous thromboembolism and to reduce the risk of stroke and systemic embolism in patients with nonvalvular atrial fibrillation. Because apixaban and rivaroxaban are predominantly eliminated by cytochrome P450 (CYP) 3A and P‐glycoprotein (P‐gp), concomitant use of combined P‐gp and strong CYP3A4 inhibitors and inducers should be avoided. Physiologically‐based pharmacokinetic models for apixaban and rivaroxaban were developed to estimate the net effect of CYP3A induction, P‐gp inhibition, and P‐gp induction by rifampicin. The disposition of rivaroxaban is more complex compared with apixaban because both hepatic and renal P‐gp is considered to contribute to rivaroxaban elimination. Furthermore, organic anion transporter‐3, a renal uptake transporter, may also contribute the elimination of rivaroxaban from systemic circulation. The models were verified with observed clinical drug-drug interactions with CYP3A and P‐gp inhibitors. With the developed models, the predicted area under the concentration time curve and maximum concentration ratios were 0.43 and 0.48, respectively, for apixaban, and 0.50-0.52 and 0.72-0.73, respectively, for rivaroxaban when coadministered with 600 mg multiple doses of rifampicin and that were very close to observed data. The impact of each of the elimination pathways was assessed for rivaroxaban, and inhibition of CYP3A led to a larger impact over intestinal and hepatic P‐gp. Inhibition of renal organic anion transporter‐3 or P‐gp led to an overall modest interaction. The developed apixaban and rivaroxaban models can be further applied to the investigation of interactions with other P‐gp and/or CYP3A4 inhibitors and inducers.